Modulation of myeloid and T cells in vivo by Bruton’s tyrosine kinase inhibitor ibrutinib in patients with metastatic pancreatic ductal adenocarcinoma - Li Zhang; Matthew Crocker; Lawrence Fong; Lisa M Coussens; Charles D Lopez; Shamilene Sivagnanam; Meenal Sinha; Brandon Chen; Jaqueline Marquez; Alexander Cheung; Whitney Tamaki; Jacob Stultz; et al. (Journal for ImmunoTherapy of Cancer)
Background In preclinical studies of pancreatic ductal adenocarcinoma (PDAC), ibrutinib improved the antitumor efficacy of the standard of care chemotherapy. This led to a phase 1b clinical trial to determine the safety, tolerability, and immunologic effects of ibrutinib treatment in patients with advanced PDAC.Methods Previously untreated patients with PDAC were enrolled in a phase 1b clinical trial (ClinicalTrials.gov) to determine the safety, toxicity, and maximal tolerated dose of ibrutinib when administered with the standard regimen of gemcitabine and nab-paclitaxel. To study the immune response to ibrutinib alone, the trial included an immune response arm where patients were administered with ibrutinib daily for a week followed by ibrutinib combined with gemcitabine and nab-paclitaxel. Endoscopic ultrasonography-guided primary PDAC tumor biopsies and blood were collected before and after ibrutinib monotherapy. Changes in abundance and functional state of immune cells in the blood was evaluated by mass cytometry by time of flight and statistical scaffold analysis, while that in the local tumor microenvironment (TME) were assessed by multiplex immunohistochemistry. Changes in B-cell receptor and T-cell receptor repertoire were assessed by sequencing and analysis of clonality.Results In the blood, ibrutinib monotherapy significantly increased the frequencies of activated inducible T cell costimulator+(ICOS+) CD4+ T cells and monocytes. Within the TME, ibrutinib monotherapy led to a trend in decreased B-cell abundance but increased interleukin-10+ B-cell frequency. Monotherapy also led to a trend in increased mature CD208+dendritic cell density, increased late effector (programmed cell death protein 1 (PD-1–) eomesodermin (EOMES+)) CD8+ T-cell frequency, with a concomitantly decreased dysfunctional (PD-1+ EOMES+) CD8+ T-cell frequency. When ibrutinib was combined with chemotherapy, most of these immune changes were not observed. Patients with partial clinical responses had more diverse T and B cell receptor repertoires prior to therapy initiation.Conclusion Ibrutinib monotherapy skewed the immune landscape both in the circulation and TME towards activated T cells, monocytes and DCs. These effects were not observed when combining ibrutinib with standard of care chemotherapy. Future studies may focus on other therapeutic combinations that augment the immunomodulatory effects of ibrutinib in solid tumors.Trial registration number NCT02562898.